Microbial Evaluation and Solar Disinfection of Hand dug wells, Rivers and Swimming Pools in Port-Harcourt Metropolis - Akomah-Abadaike, Onyinyechi Ndimele; Duke, O. C. S (European Journal of Applied Sciences, 2024)
Rivers and wells are sources of water for most rural dwellers as they serve as the common source of water used for domestic chores. This study investigated the microbiological quality of rivers, wells, swimming pool which are located in Ogbogoro, Choba, Iwofe all in Port Harcourt metropolis. Standard microbiological and physiochemical methods were used to ascertain the microbial and physiochemical quality of the water samples. The pH values ranged from 5.5 – 6.94. A total of eleven bacteria genera were isolated; they are Klebsiella spp (4.84 %), Enterococci (8.06 %), Pseudomonas spp (14.52 %), Salmonella (6,45 %) Staphylococci spp (24.19 %), Bacillus spp (6.45 %), Shigella spp (4.84 %), Streptococci spp (3.23 %), Enterobacter spp (6.45 %), Vibrio cholera (1.61 %) and E. coli (8.06 %). The total heterotrophic bacteria count ranged from log 5.07 – log 8.44 cfu/ml. Coliform count showed values log 2.27 – log 6.86 cfu/ml. Salmonella-Shigella count ranged from 0 – log 6.65 cfu/ml. Nine fungi general were identified: Aspergillus niger, Mucur sp., Aspergillus flavus, Candida sp., Fusarium sp., Penicillium sp., Trichophyton sp., Rhizopus, Rhizopus stolo. Exposure of river and well samples to solar showed that there was a huge reduction in microbial load; log 5.47 cfu/ml to log 0 cfu/ml and log 5.18 cfu/ml – log 0 cfu/ml for river and well respectively. The result shows that the investigated pools, rivers and wells were contaminated with pathogenic microorganisms due to insufficient treatment, inadequate management and poor hygiene of bathers. It is therefore recommended the proper treatment of water before use for domestic purposes especially when sourced from rivers and wells, appropriate maintenance and monitoring.